Minimizing Surgical Blood Loss at Cesarean Hysterectomy for Placenta Previa With Evidence of Placenta Increta or Placenta Percreta: The State of Play in 2020. Issue 2 (June 2021) - Kingdom, J.C.; Hobson, S.R.; Murji, A.; Allen, L.; Windrim, R.C.; Lockhart, E.; Collins, S.L.; Soleymani Majd, H.; Alazzam, M.; Naaisa, F.; Shamshirsaz, A.A.; Belfort, M.A.; et al.
Abstract : ( Am J Obstet Gynecol . 2020;223:322–329) Placenta accreta spectrum (PAS) is associated with notable surgical risks, especially in cases of placenta previa-percreta. Surgical blood loss is the key cause of morbidity or mortality in surgery for PAS. Multidisciplinary management of PAS has developed and improved, leading clinicians to reexamine the use of interventional radiology techniques and ligation of the anterior divisions of the internal iliac arteries. This article reports on developments in the care of patients with PAS, specifically those undergoing elective cesarean hysterectomy for placenta previa-percreta.